2011
DOI: 10.1097/prs.0b013e3181fed511
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Lymphatic Drainage Pattern of the Head and Neck: Further Anatomic Studies and Clinical Implications

Abstract: An actual and accurate lymphatic map of the head and neck lymphatic drainage patterns is presented to upgrade our anatomical knowledge. This map will be of benefit for the clinical management of trauma and malignancies in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…Examples of these pathways in the upper limb include the tricipital pathway (‘Caplan's pathway’), which is closely associated with the triceps muscle,8 and the cephalic pathway (‘Mascagni's pathway’), a superficial pathway from the forearm, crossing over the clavicle en route to the cervical chain 9 10. Variation in lymphatic drainage patterns has also been evidenced using modern techniques of lymphatic mapping 11. This has been demonstrated in patients with cutaneous melanomas, where lymphatic drainage can be highly variable 12…”
Section: Discussionmentioning
confidence: 98%
“…Examples of these pathways in the upper limb include the tricipital pathway (‘Caplan's pathway’), which is closely associated with the triceps muscle,8 and the cephalic pathway (‘Mascagni's pathway’), a superficial pathway from the forearm, crossing over the clavicle en route to the cervical chain 9 10. Variation in lymphatic drainage patterns has also been evidenced using modern techniques of lymphatic mapping 11. This has been demonstrated in patients with cutaneous melanomas, where lymphatic drainage can be highly variable 12…”
Section: Discussionmentioning
confidence: 98%
“…Pan et al reported that the lymphatic pathway proceeds via 3 layers in the lateral cervical region: subcutaneous, intermuscular, and perivascular layers. In this case, the deep flow of bilateral lymphatic pathways (the intermuscular and perivascular layers) was dissected and, therefore, disrupted by neck dissections.…”
Section: Discussionmentioning
confidence: 99%
“…14 Human cadaver studies suggest that lymphatics from the lateral upper and lower eyelids drain primarily into the parotid lymph nodes and that the lymphatics from the medial upper and lower eyelids drain into the submandibular nodes. 15 For the conjunctiva, the lateral half is known to drain into the parotid region, and the medial half into submandibular and deeper cervical nodes. 16,17 Lymphoscintigraphic mapping in non-diseased human subjects revealed that lymphatics in the upper and lower eyelids, both medial and lateral portions, drain most frequently to the preauricular nodes.…”
Section: Lymphatic Drainage Of the Eyelids And Conjunctivamentioning
confidence: 99%